2021
DOI: 10.1530/rep-21-0236
|View full text |Cite
|
Sign up to set email alerts
|

Expression and role of resistin on steroid secretion in the porcine corpus luteum

Abstract: Resistin plays an important role in adipogenesis, obesity, insulin resistance and reproduction. Previous studies showed resistin action on ovarian follicular cells; however, whether resistin regulates steroid secretion in luteal cells is still unknown. Our aim was first to determine the expression of resistin and its potential receptors (tyrosine kinase-like orphan receptor 1 [ROR1] and Toll-like receptor 4 [TLR4]) in the porcine corpus luteum (CL), regulation of its expression, effect on kinases phosphorylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…This study revealed that resistin has an inhibitory effect on granulosa cell steroidogenesis in bovine ovaries, but has a stimulatory effect on P4 secretion in rats [60]. In a recent study, it was observed that resistin decreased progesterone (P4) levels, increased estradiol (E2) levels, and regulated various pathways, such as those of steroidogenic acute regulatory protein (STAR), cholesterol side-chain cleavage enzyme, 3β-hydroxysteroid dehydrogenase, estrogen synthetase, through the activation of protein kinase A and mitogen-activated protein kinase 1 [61]. This study provides further evidence for the complex effects of resistin on reproductive function.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that resistin has an inhibitory effect on granulosa cell steroidogenesis in bovine ovaries, but has a stimulatory effect on P4 secretion in rats [60]. In a recent study, it was observed that resistin decreased progesterone (P4) levels, increased estradiol (E2) levels, and regulated various pathways, such as those of steroidogenic acute regulatory protein (STAR), cholesterol side-chain cleavage enzyme, 3β-hydroxysteroid dehydrogenase, estrogen synthetase, through the activation of protein kinase A and mitogen-activated protein kinase 1 [61]. This study provides further evidence for the complex effects of resistin on reproductive function.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, resistin displayed elevated levels at 0.5 h, 2 h, 4 h, and 12 h, followed by a decrease at the 64 h mark (Figure 3). Studies have reported that resistin can elevate estradiol (E2) levels, reduce P4 levels, and regulate several pathways, including those associated with steroidogenic acute regulatory protein (STAR), cholesterol side-chain cleavage enzyme, 3β-hydroxysteroid dehydrogenase, and estrogen These effects are brought about through the activation of protein kinase A and mitogen-activated protein kinase 1 [37,60]. Visfatin is another adipokine that plays a role in various physiological processes, including metabolism and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been established that the ovary is receptive to the effects of adipokines. Research has unveiled that these adipokines influence mechanisms linked to steroid synthesis and can modulate the production of crucial factors like P4 and PGs, which are pivotal regulators of CL longevity [36][37][38]. Consequently, adipokines have emerged as a class of factors that potentially significantly regulate CL function during luteal regression.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we noted that the inhibitory effect of SPX on KGN proliferation was linked to activation of GALR2/3 receptors, as well as MAP3/1, AKT, and STAT3 kinase, while E2 synthesis was linked to both receptors, MAP3/1 and PKA activation. Inhibition of PKA was previously described as connected with decreased P4 synthesis by porcine corpus luteum [65], thus inhibition of phosphorylation may be an answer to negative SPX action on proliferation and E2 synthesis. Similarly, Roche [66] and Maillard [67] showed that other adipokines like apelin and adiponectin increased steroidogenesis by the MAP3/1 pathway in human and bovine ovarian cells, whereas chemerin decreased IGF1-induced steroidogenesis by inhibiting MAP3/1 phosphorylation and proliferation due to the inhibition of the AKT pathway in human GC [50].…”
Section: Discussionmentioning
confidence: 99%